2013
DOI: 10.1177/000313481307900815
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Early Mortality after Trauma in a Neighborhood Urban Trauma Center: Can We Improve Outcomes?

Abstract: Even with specialized trauma systems, a significant number of deaths occur within the early postinjury period. Our goal was to examine deaths within this period for cause and determine if care could improve outcomes. A retrospective chart review was performed on all patients who were dead on arrival or died within 4 hours of arrival between January 1, 2005, and December 31, 2011. Survival probabilities and Injury Severity Score (ISS) were calculated. Chart review and trauma review processes were used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Haemorrhage control was done correctly in 70% in our study vs. 60% in the German/Austrian study, and hypothermia prevention correctly in 62% vs. 42%. In other studies, first aid has been provided correctly in a range from 10.5% to 65% of cases . It is feasible that the difference is due to patients being more lightly injured in our study, or because our study area largely comprises rural areas where bystanders may have had more time to perform measures before the arrival of the EMS than in urban areas, where EMS response times may be shorter.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Haemorrhage control was done correctly in 70% in our study vs. 60% in the German/Austrian study, and hypothermia prevention correctly in 62% vs. 42%. In other studies, first aid has been provided correctly in a range from 10.5% to 65% of cases . It is feasible that the difference is due to patients being more lightly injured in our study, or because our study area largely comprises rural areas where bystanders may have had more time to perform measures before the arrival of the EMS than in urban areas, where EMS response times may be shorter.…”
Section: Discussionmentioning
confidence: 92%
“…Reported results, though scarce, are interesting, suggesting that bystander first aid resulted in a possible improvement in survival of 1.8–5%, but how often and how well first aid was provided varied greatly . Two recent studies have reported that injuries were potentially survivable in 6–20% of trauma victims who died either at the scene of injury, during ambulance transportation, or within 4 h of hospital arrival . Thus, optimization of first responder actions may improve survival.…”
mentioning
confidence: 99%
“…Inadequate fluid resuscitation and hemorrhage control were the leading causes of death [ 23 ] among definitely preventable deaths. Inadequate fluid resuscitation was a common problem found in other similar LMIC studies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients without signs of life on arrival (i.e., heart rate = 0, systolic blood pressure = 0 and motor component of the Glasgow Coma Scale [GCS] = 1) were also excluded in the belief that they were unable to be resuscitated, regardless of quality of care received. 13…”
Section: Assembly Of Study Cohortmentioning
confidence: 99%